The Effect of Timeliness of Care on Lung Cancer Survival - A Population-Based Approach - Teresa Guerreiro; Alexandra Mayer; Pedro Aguiar; António Araújo; Carla Nunes (Ubiquity Press, 2023)
Background: Timeliness of care is an important dimension of healthcare quality but it's unclear whether it improves clinical outcomes in lung cancer (LC) patients. Objectives: This study aims to analyze treatment patterns, time-to-treatment (TTT) and the impact of treatment timeliness (TT) in overall survival (OS) of patients diagnosed with LC in 2009-2014 in a population-based registry from Southern Portugal. Materials and Methods: We estimated median TTT for overall population, treatment type and stage. The impact of treatment and TT on five-year OS was analyzed using the Kaplan-Meier method and Cox regression modelling to determine the hazard ratio (HR) of death associated with treatment and TT. Results: From the 11,308 cases diagnosed, 61.7% received treatment. Treatment rate decreased with increasing stage from 88% in stage I to 66.1% in stage IV. Overall median TTT was 49 days (IQR: 28-88) and 43.3% received TT. Surgery had a longer TTT than radiotherapy and systemic treatment. Patients in earlier stages had lower TT rates and longer TTT compared to more advanced, 24.7% and 80 days in stage I versus 51.3% and 42 days in stage IV (p < 0.0001). OS was 14.9% for total population and 19.6% and 7.1% for patients with and without treatment registered, respectively. TT had no observed impact on OS for stages I/II but a negative effect for stages III/IV. Relative to treated, the adjusted mortality risk was higher in untreated patients (HR = 2.240; 95%CI: 2.293-2.553). Contrary to treatment, TT had a negative impact on survival, with 11.3% in timely vs. 21.5% in untimely treated. Compared to untimely treated, the risk of death in TT patients was 46.6% higher (HR = 1.465; 95%CI: 1.381-1.555). Conclusions: LC survival is highly dependent on early diagnosis and adequate treatment. Time-to-treatment was longer than recommended for all treatment types but particularly for surgery. Overall TT results were paradoxical, as better survival was observed in patients untimely treated. The factors associated with TT were not possible to analyze and its impact on patient outcomes remains unclear. However, it is important to assess quality-of-care to improved LC management.